2022
DOI: 10.1186/s12889-022-13791-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with loss to follow up among HIV-exposed children: a historical cohort study from 2000 to 2017, in Porto Alegre, Brazil

Abstract: Background There are many inequalities in terms of prevention and treatment for pregnant women with HIV and exposed children in low and middle-income countries. The Brazilian protocol for prenatal care includes rapid diagnostic testing for HIV, compulsory notification, and monitoring by the epidemiological surveillance of children exposed to HIV until 18 months after delivery. The case is closed after HIV serology results are obtained. Lost to follow-up is defined as a child who was not located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…A recent East African cohort study demonstrated that APW-HIV-positive who were older than 15 years old had approximately twice the chance of becoming lost to follow-up from HIV clinics than male teenagers [ 55 ]. On the other hand, a Brazilian historical cohort study found that a younger maternal age was an independent risk factor for being lost to follow-up for HIV-exposed children during the first 18 months of surveillance [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent East African cohort study demonstrated that APW-HIV-positive who were older than 15 years old had approximately twice the chance of becoming lost to follow-up from HIV clinics than male teenagers [ 55 ]. On the other hand, a Brazilian historical cohort study found that a younger maternal age was an independent risk factor for being lost to follow-up for HIV-exposed children during the first 18 months of surveillance [ 56 ].…”
Section: Discussionmentioning
confidence: 99%